2019
DOI: 10.5897/jpbcs2018.0783
|View full text |Cite
|
Sign up to set email alerts
|

Genetic action and potence ratio of maize in an 88 diallel cross growing under saline condition

Abstract: Twenty-eight hybrids of Zea mays L. produced in 2015-16 from 8×8 half diallel mating design were evaluated along with their parents in 2016-2017 under saline condition to find out genetic action and potency ratio of some agronomic and yield contributing traits. Genetic action and potency ratio were analyzed following Hayman's diallel analyses and Smith's formula, respectively. Genetic parameter like additive variance (D), dominance variance (H 1), proportion of positive and negative genes in the parents (H 2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These findings align with previous researches by Chaudhari et al [ 44 ] and Nagar et al [ 45 ], who also reported overdominance behavior for days to 50 % heading, number of spikelets per spike, and thousand grain weight in bread wheat. Rohman et al [ 46 ] observed overdominance behavior in plant height, days to 50 % tasseling, days to 50 % silking, and 100-GW in maize.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with previous researches by Chaudhari et al [ 44 ] and Nagar et al [ 45 ], who also reported overdominance behavior for days to 50 % heading, number of spikelets per spike, and thousand grain weight in bread wheat. Rohman et al [ 46 ] observed overdominance behavior in plant height, days to 50 % tasseling, days to 50 % silking, and 100-GW in maize.…”
Section: Discussionmentioning
confidence: 99%
“…The potency ratio is a value used to determine gene action in progeny resulting from crosses. Research conducted by Rohman et al (2019) concluded that the value of the potency ratio is important h. Sweetness Level to know to estimate the level of dominance of genes that play a role in the inheritance of plant traits.…”
Section: Genetic Informationmentioning
confidence: 99%